Memory illusions and category malleability: False recognition for goal-derived reorganizations of common categories. - Soro, Jerônimo C.; Ferreira, Mário B.; Carneiro, Paula; Moreira, Sérgio (Memory & Cognition, 2020)
Four studies explore semantic memory intrusions for goal-derived subcategories (e.g., "sports good for backache") embedded in taxonomic categories (e.g., "sports"). Study 1 presented hybrid lists (composed of typical items from both representations: taxonomic categories and subcategories) together with names of subcategories, names of taxonomic categories, or with no names. Subcategory names produced levels of false recognitions for critical lures from subcategories comparable with critical lures from taxonomic categories. Study 2 presented lists of exemplars either from taxonomic categories or subcategories (between participants). Lists of subcategories paired with their names produced higher levels of false recognition for subcategories lures compared with taxonomic lures. Study 3 replicated this result and showed that even though distinctiveness of taxonomic lures in a subcategory context (i.e., subcategory list with a subcategory name) may facilitate rejection of these lures, subcategory lures were still more falsely recognized than were taxonomic lures when retrieval monitoring was hindered through speeded recognition. Study 4 replicated the results with lists in which production frequency was better controlled and with a larger sample allowing for increased power of the test. Although confirming the critical role of preexistent categorical structures in the generation of false memories, results show that false memories for goal-derived subcategories can occur with the same frequency as false memories stemming from better established taxonomic categories. Such results broaden the scope of occurrence of false memories to goal-derived semantic organizations, which are often closer to categorizations used in real-world environments.